Account book of cash received for various estates (1909)
Some accounts closed before 1921. Volume gives date denominations, tenants’ names, folio no., total cash received and summaries on 1 Nov. each year.
Keywords: Kirwan family; Rentals -- Ireland -- Galway (County); Administration of estates -- Ireland -- Galway (County); Galway (Ireland)